Temporal Dynamics of Collaborative Networks in Large Scientific Consortia. Issue 5 (May 2016) - Wang, Daifeng; Yan, Koon-Kiu; Rozowsky, Joel; Pan, Eric; Gerstein, Mark
Abstract : The emergence of collective creative enterprise such as large scientific consortia is a unique feature in modern scientific research. We analyzed the temporal co-authorship network structures of ENCODE and modENCODE consortia. Our analysis revealed that the consortium members work closely as a community whereas non-members collaborate in the scale of a few laboratories. We also identified a few brokers playing an important role to facilitate collaborations with outside researchers.